2010
DOI: 10.1108/03684921011021255
|View full text |Cite
|
Sign up to set email alerts
|

Requisitely holistic ethics planning as pre‐condition for enterprise ethical behaviour

Abstract: Purpose-Ethical behaviour of enterprises can be attained only by planning of ethics. The purpose of this paper is to show the need for the business ethics planning, to disclose the need for the requisitely holistic planning of enterprise ethics, and to offer the concept of the requisitely holistic planning of enterprise ethics. Design/methodology/approach-The research cognitions on the importance of ethical core values, enterprise culture, ethical climate and informal as well as formal measures of business eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Delineating and categorizing EBP is challenging, but prior research is instructive in this exercise (McDonald and Nijhof ), in assessing the ethicality of an organization's dealings with its stakeholders (Spiller ), and in evaluating methods of business ethics implementation (Belak et al. ). McDonald and Nijhof () developed a model for ethics program implementation as a means of stimulating morally responsible behavior in organizations.…”
Section: Composition and Communication Of Ebpmentioning
confidence: 99%
See 1 more Smart Citation
“…Delineating and categorizing EBP is challenging, but prior research is instructive in this exercise (McDonald and Nijhof ), in assessing the ethicality of an organization's dealings with its stakeholders (Spiller ), and in evaluating methods of business ethics implementation (Belak et al. ). McDonald and Nijhof () developed a model for ethics program implementation as a means of stimulating morally responsible behavior in organizations.…”
Section: Composition and Communication Of Ebpmentioning
confidence: 99%
“…Another study showed how ethical behavior in organizations is contingent on a more holistic and principled approach to business planning (Belak et al. ). This perspective utilizes measures to assess the influence of ethical values on organization systems and behavior and the evaluation of an organization's ethical stance by salient stakeholder groups.…”
Section: Composition and Communication Of Ebpmentioning
confidence: 99%
“…A code of ethics by itself does not provide adequate ethical decision-making for every circumstance, so it should be used in accordance with the actual decision and adjusted if necessary. However, one must also consider the fact that a code of ethics is a way of ensuring enterprise's ethical practices and that the enterprise ethics (Belak, Je. et al, 2010) One of the important principles of corporate social responsibility (CSR) in ISO 26000 (ISO, 2010) is ethical behavior.…”
Section: Ethical Routine Decision-makinga Case Of Febmentioning
confidence: 99%
“…In their research Belak et al (2010) argued that in order to achieve the optimal e¤ectiveness level of business by ethical behaviour, the initiated measures of business ethics should never be implemented as isolated tools, but only in the frame of a full and complete ethics program. The initiated business ethics measures have to be correctly adjusted and coordinated, as well as integrated, in a common business ethics concept, program or plan.…”
Section: Borut Milfelner Jernej Belak -Integral Aproach To Enterprismentioning
confidence: 99%
“…Various researches show that enterprise culture with its values is of essential meaning by fostering business ethics in a sense of assuring enterprise's success (e.g. Belak and Milfelner, 2011;Belak et al, 2010;Belak and Mulej, 2009). Hofstede (1998aHofstede ( , 1998b argues that enterprise culture as the collective programming of the mind distinguishes participants of one enterprise from another.…”
Section: Introductionmentioning
confidence: 99%